Anti-Bovine Programmed Death-1 Rat–Bovine Chimeric Antibody for Immunotherapy of Bovine Leukemia Virus Infection in Cattle - Okagawa, Tomohiro; Konnai, Satoru; Nishimori, Asami; Maekawa, Naoya; Ikebuchi, Ryoyo; Goto, Shinya; Nakajima, Chie; Kohara, Junko; Ogasawara, Satoshi; Kato, Yukinari; Suzuki, Yasuhiko; Murata, Shiro; et al. (Frontiers in Immunology, 2017)
Blockade of immunoinhibitory molecules, such as programmed death-1 (PD-1)/PD-ligand 1 (PD-L1), is a promising strategy for reinvigorating exhausted T cells and preventing disease progression in a variety of chronic infections. Application of this therapeutic strategy to cattle requires bovinized chimeric antibody targeting immunoinhibitory molecules. In this study, anti-bovine PD-1 rat–bovine chimeric monoclonal antibody 5D2 (Boch5D2) was constructed with mammalian expression systems, and its biochemical function and antiviral effect were characterized in vitro and in vivo using cattle infected with bovine leukemia virus (BLV). Purified Boch5D2 was capable of detecting bovine PD-1 molecules expressed on cell membranes in flow cytometric analysis. In particular, Biacore analysis determined that the binding affinity of Boch5D2 to bovine PD-1 protein was similar to that of the original anti-bovine PD-1 rat monoclonal antibody 5D2. Boch5D2 was also capable of blocking PD-1/PD-L1 binding at the same level as 5D2. The immunomodulatory and therapeutic effects of Boch5D2 were evaluated by in vivo administration of the antibody to a BLV-infected calf. Inoculated Boch5D2 was sustained in the serum for a longer period. Boch5D2 inoculation resulted in activation of the proliferation of BLV-specific CD4+ T cells and decrease in the proviral load of BLV in the peripheral blood. This study demonstrates that Boch5D2 retains an equivalent biochemical function to that of the original antibody 5D2 and is a candidate therapeutic agent for regulating anti-viral immune response in vivo. Clinical efficacy of PD-1/PD-L1 blockade awaits further experimentation with a large number of animals.